EU’s Energy Transformation Towards an Increased Share of Renewable Energy - Jadwiga ADAMCZYK; Zofia GRÓDEK-SZOSTAK; Gabriela MALIK; Agata NIEMCZYK (Communications of International Proceedings, 2021)
The foundation of the EU's energy efficiency policy is Directive 2012/27/EU on Energy Efficiency. It establishes a set of measures to enable achieve EU’s 20% energy efficiency improvement target by 2020. The Directive also introduced energy saving targets and a number of energy efficiency policies and consumer rights, e.g., energy efficient renovations, mandatory energy certificates for buildings, minimum energy efficiency standards for various products, energy labelling and smart meters. The aim of the article is to verify the research hypothesis, i.e., whether all European countries will achieve the EU target of 20% share of renewable energy by 2020. The formal part of assessing the achievement of the RES target and the European Committee's decision on possible consequences for the countries that will fail to do so will start in 2022. The legal foundation of the process will be two documents, the first being the final report of the share of RES in the energy mix for 2020, which will be published by the European Statistical Office EUROSTAT in early 2022.
Keywords: Management; Energy Efficiency; Energy Policy; Climate Change; Sustainable And Balanced Development